Genetic Navigation: A Narrative Review of XRCC1 Polymorphism Impact on Platinum-Based Chemotherapy Outcomes in NSCLC Patients - Permatasari LI; Afifah NN; Ishmatullah MH; Intania R; Halimah E; Barliana MI (Cancer Management and Research)
Lanny Indah Permatasari,1,2 Nadiya Nurul Afifah,1 Maryam Hasymia Ishmatullah,1 Ruri Intania,3 Eli Halimah,2 Melisa Intan Barliana1,4 1Department of Biological Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, Indonesia; 2Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, Indonesia; 3Department of Pulmonology and Respiratory Medicine, Dr. H.A. Rotinsulu Lung Hospital, Bandung, Indonesia; 4Center of Excellence for Pharmaceutical Care Innovation, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, IndonesiaCorrespondence: Melisa Intan Barliana, Department of Biological Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Jalan Raya Bandung-Sumedang KM 21, Jatinangor, Sumedang, West Java, 45363, Indonesia, Tel +62 22 842888888, Email melisa.barliana@unpad.ac.idAbstract: Non-small cell lung cancer (NSCLC) is the most common form of lung cancer, accounting for 85% of all cases, with a poor 5-year survival rate of less than 20%. The majority of NSCLC patients are diagnosed at an advanced stage, contributing to the low survival rate. Platinum-based chemotherapy, including cisplatin and carboplatin, remains the cornerstone of treatment for advanced NSCLC. However, DNA repair mechanisms often hinder treatment efficacy, notably Base Excision Repair (BER), mediated by the X-ray Repair Cross Complementing 1 (XRCC1) protein. This review aims to investigate the role of XRCC1 polymorphisms in platinum resistance, focusing on their impact on DNA repair efficiency. XRCC1’s involvement in the BER pathway is critical for repairing DNA damage caused by platinum agents, and polymorphisms in XRCC1 have been linked to altered repair capacity, influencing clinical outcomes and resistance to platinum-based chemotherapy in NSCLC patients.Keywords: non-small cell lung cancer, DNA repair, base excision repair, XRCC1 polymorphism, platinum-based chemotherapy, response therapy, toxicity, survival rates, Platinum-based